JURIDICAL REVIEW OF THE GRANTING OF INHERITANCE RIGHTS TO DAUGHTERS IN BALINESE CUSTOMARY LAW BASED ON THE DECISION OF THE THIRD GREAT ASSEMBLY (PESAMUHAN AGUNG III) OF THE MAIN COUNCIL OF PAKRAMAN VILLAGES (MUDP) BALI IN 2010. DECISION NO. 01/KEP/PSM-3MD - Rajuniper Manurung; Ni Ketut Sari Adnyani; Komang Febrinayanti Dantes (Jurnal Pacta Sunt Servanda, 2025)
The purpose of this study is to find out the implementation of the Decision of the Pesamuhan Agung III Majelis Utama Desa Pakraman (MUDP) regarding the distribution of inheritance for Balinese Hindu women and explain the obstacles faced in implementing this decision. The research method that used is a normative juridical approach with a qualitative analysis method, using data collection techniques through primary, secondary, and tertiary legal materials. The results of the research is that the 2010 MUDP Decision is a progressive step that opens opportunities for Balinese Hindu daughters to obtain inheritance rights, although proportionally only half of what male heirs receive and still subject to certain conditions. The legal consequences of granting inheritance rights to women in the Balinese customary law community indicate a significant normative change, although it has not yet been fully realized in practice.